Enhanced electroforced sedimentation of various solid-liquid systems - Jami, Mohammed Saedi; Iwata, Masashi; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail; Al-Khatib, Ma'an Fahmi Rashid; Mujeli, Mustapha (Academic Journals, 2011)
This study presents the results of experimental work carried out to evaluate the role of polyacrylamide as dewatering aid in electroforced sedimentation. Electroforced sedimentation experiments under constant electric current density of zinc oxide and kaolin suspended in aqueous media with and without polyacrylamide were carried out and comparison was made between the experimental results and model predictions. The model solution of basic differential equation was used to measure the progress of electroforced sedimentation, represented by an average consolidation ratio Uc as in mechanical expression. The addition of polyacrylamide as a dewatering aid enhanced the electroforced sedimentation.